Melding Multiple Sources of Knowledge: Using Theory and Experiential Knowledge to Design a Community Health Intervention Study - Mina Silberberg; Lawrence H. Muhlbaier; Elaine Hart-Brothers; Glenda M. Small; Arwen E. Bunce; Rupal Patel; Seronda Robinson; Sherman A. James (Journal of Participatory Research Methods)
Although Community-Based Participatory Research (CBPR) is grounded in socioecological theories of health, using and addressing theory in CBPR can be challenging. This paper explores how theory was used and melded with community expertise in one CBPR study in Durham, North Carolina. Challenges to use of theory included time restrictions, the need to focus on meeting local needs and making short-term measurable gains, and differences among collaborators in comfort with and concern for theoretical discussion. Both community and theoretical voices were sometimes short-changed -- particularly voices that were more difficult to access or integrate into existing ways of operating. Nonetheless, we were able to bring theory into our work at a number of stages and to meld theory with community expertise in ways that benefited our project. Our case study suggests the importance of creating opportunities for small group discussion; utilizing an iterative dialogic approach to melding theory and community expertise; grounding theoretical discussions in specific, concrete questions; taking the long view of CBPR, including purposefully bringing attention to theory even while responding to pragmatic concerns; and spending more time on building the capacity to collaborate of both academic and community partners. It also raises the need for funders to consider how to align their expectations of grantees with effective attention to root causes of poor health and health disparities.